Complex tibial plateau fractures: a retrospective study and proposal of treatment algorithm. (October 2017) - Menghi, Amerigo; Mazzitelli, Giuseppe; Marzetti, Emanuele; Barberio, Francesco; D'Angelo, Emanuela; Maccauro, Giulio
Abstract: Introduction: Complex tibial plateau fractures are characterized by compression and sinking of one or both the articular surfaces. In this study, we evaluated clinical and radiological outcomes in patients with 41.C1, 41.C2, 41.C3 fractures according to AO classification. We also provide a specific therapeutic algorithm for each type of fracture. Material and Methods: The study was conducted in 43 patients who underwent surgical treatment for complex tibial plateau fractures and were followed for a minimum of 12 months. Outcome measures included: range of motion (ROM) recovery, Short Form 36 Health Survey (SF36), Knee injury and Osteoarthritis Outcome Score (KOOS), tibial plateau angle (TPA), and posterior angle (PA). Results: Analyses were performed in 38 patients after excluding 5 cases because of missing imaging evaluations at follow-up. All patients showed good quality of life in all areas considered by SF36 and KOOS as well as satisfactory recovery of ROM. Average TPA and PA values were 87.9° and 0.6°, respectively. Discussion: In complex tibial plateau fractures, surgical treatment is instrumental to obtain full restoration of the joint surface and fast functional recovery. Results are highly related to the type of treatment adopted for different kinds of fracture. In our case series, the best results were obtained when 41.C1 fractures were treated with a single plate. In 41.C2 fractures, clinical and imaging outcomes were independent of the number of plates used. In contrast, in 41.C3 fractures, optimal results were achieved with double plates. Conclusions: Based on our findings, as also supported by the literature, 41.C1 fractures should be treated with single plate, which reduces the surgical time, soft tissue damage and infection risk. On the other hand, 41.C3 fractures have best outcomes in stability, consolidation and recovery time when treated with double plate.